1969
DOI: 10.2134/agronj1969.00021962006100010031x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Planting Rates and Mowing on Yield and Quality of Crimson Clover Seed1

Abstract: In a 3‐year experiment we studied the effects of difterent planting rates and of early spring mowing on yields and quality of crimson clover seed. High planting rates generally hastened plant development and maturity. In non‐mowed stands, the 5.6 and 9 kg/ha planting rates resulted, in the best seed yields. Mowing generally increased seed yields, germination, and hard seeds, and it decreased 1,000‐seed weight as compared with non‐mowing. Planting at 13.4 kg/ha plus mowing resulted in the most seed. ]Low planti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
4
0
1

Year Published

1971
1971
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…The weight of untreated seeds ranged from 4.89 to 5.67 mg, whereas the weight of TE‐treated seeds ranged from 4.24 to 5.43 mg. Seed weights in crimson clover from other published reports were noted to be in the range of 2.30 to 4.90 mg (Iannucci and Martiniello, 1998; Iannucci et al, 1996; Martiniello, 1999; Rampton, 1969); thus, the seed weight found in this study was high by comparison. Rampton (1969) did not find any differences in seed germination across the range of seed weights similar to those observed for the TE‐treated seed in this study; therefore, it is unlikely that the lower weight seed evident in TE treatments caused reduced seed germination.…”
Section: Discussionsupporting
confidence: 54%
“…The weight of untreated seeds ranged from 4.89 to 5.67 mg, whereas the weight of TE‐treated seeds ranged from 4.24 to 5.43 mg. Seed weights in crimson clover from other published reports were noted to be in the range of 2.30 to 4.90 mg (Iannucci and Martiniello, 1998; Iannucci et al, 1996; Martiniello, 1999; Rampton, 1969); thus, the seed weight found in this study was high by comparison. Rampton (1969) did not find any differences in seed germination across the range of seed weights similar to those observed for the TE‐treated seed in this study; therefore, it is unlikely that the lower weight seed evident in TE treatments caused reduced seed germination.…”
Section: Discussionsupporting
confidence: 54%
“…Assim, essa característica, dependendo da sua variabilidade em determinada população, pode mostrar-se significativa na determinação do rendimento de sementes. Além disso, essa variável também é importante, por refletir o vigor das sementes e, em trevo vermelho, pode ser influenciada por vários fatores, como: umidade, temperatura, corte das plantas, vigor da haste na qual as sementes são formadas, precocidade etc (Winch & Tossel, 1960;Howkins, 1965;Rampton, 1969;Clifford & Anderson, 1979).…”
Section: Resultsunclassified
“…Several authors (Argel and Humphreys, 1983; Archer, 1990) have reported that forage legumes produce more hard seeds in hotter and drier conditions. Also, Rampton (1969) found a higher hard seed content in mowed than in unmowed crimson clover ( T. incarnatum L.); he stated that, after mowing, plants undergo stress and mature later (i.e., when conditions are drier). In mechanically threshed seeds (Exp.…”
Section: Discussionmentioning
confidence: 99%